Phenolic compounds from Usnea baileyi (Stirt.) Zahlbr growing in Lam Dong province - Van Kieu Nguyen; Thuc Huy Duong (Vietnam Journal of Science, Technology and Engineering, 2019)
This study entails a continuation of the phytochemical study regarding the lichen Usnea baileyi collected in Lam Dong province. Eight compounds, 8’-O-methylprotocetraric acid (1), protocetraric acid (2), virensic acid (3), subvirensic acid (4), barbatic acid (5), diffractaic acid (6), 4-O-demethylbabartic acid (7), and atranorin (8), were isolated using various chromatographic methods. Their chemical structures were elucidated through spectroscopic analysis as well as through a comparison of their data with that in the literature.